2010
DOI: 10.1111/j.1945-5100.2010.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Diogenites as polymict breccias composed of orthopyroxenite and harzburgite

Abstract: Abstract-A few relatively unbrecciated olivine-rich diogenites consist of an equilibrium assemblage of olivine and magnesian orthopyroxene (harzburgite). More common diogenites with smaller amounts of olivine are breccias containing two distinct orthopyroxenes-one magnesian and one ferroan. These diogenites are mixtures of a harzburgite lithology that is more magnesian, with the ''normal'' orthopyroxenite lithology that is ferroan and may contain small amounts of plagioclase. Both lithologies likely formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
243
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(264 citation statements)
references
References 32 publications
18
243
2
1
Order By: Relevance
“…The diogenites are coarse-grained cumulates that formed in fractionally-crystallized magmas (Bowman et al 1997); the existence of olivine-bearing diogenites (Beck and McSween 2010) indicate that these magmas did not crystallize orthopyroxene alone. The diogenites constitute the deepest component of the layered crust model (Takeda 1997).…”
Section: Crustal Structurementioning
confidence: 99%
“…The diogenites are coarse-grained cumulates that formed in fractionally-crystallized magmas (Bowman et al 1997); the existence of olivine-bearing diogenites (Beck and McSween 2010) indicate that these magmas did not crystallize orthopyroxene alone. The diogenites constitute the deepest component of the layered crust model (Takeda 1997).…”
Section: Crustal Structurementioning
confidence: 99%
“…Asteroid differentiation is far from being completely understood and, while the majority of models favor the formation of a dunite mantle (e.g. Mason, 1962;Ruzicka et al, 1997), there are others that have suggested alternative asteroidal mantle materials such as harzburgite (Righter and Drake, 1997;Beck and McSween, 2010), high-Ca pyroxene rich cumulates , and even a relict layer of highly metamorphosed chondritic material (McCoy et al, 2006).…”
Section: Rg Mayne Et Al / Icarus 214 (2011) 147-160mentioning
confidence: 99%
“…There are two main mechanisms suggested for the formation of ferroan diogenites: that they formed from different parental melts relative to the more typical Mg-rich diogenites (Yamagchi et al, 2009); they are produced late in a sequence of fractional crystallization within individual magma chambers (Beck and McSween, 2010). Both of these formation mechanisms are possible within the partial melting model for Vesta.…”
Section: Implications For the Surface Of Vestamentioning
confidence: 99%
“…This region was chosen because Olivine, a mineral indicative of deep magmatic processes, was first detected in this area [55]. This mineral is never found alone in meteorites coming from Vesta-4 [56], [57], implying the use of an algorithm able to decompose spectra as a combination of mixtures of materials.…”
Section: Discussionmentioning
confidence: 99%